Development of shrimp flavor concentrate from sea shrimp heads by enzymatic hydrolysis. - Nuñal, Sharon N. (College of Fisheries, University of the Philippines in the Visayas, 2001)
Shrimp flavour concentrate was developed by enzymatic hydrolysis levels: 0.3%, 0.5% and 0.6% was subjected to three temperatures of 30 C,, 45 C an 60 C where amino-N content was monitored every 30 minutes interval by formula titration with a hydrolysis time 0f 0-120 minutes. The combination, which yielded the highest amino-N/ml sample content, was 0.5% enzyme concentration at 60 C for a reaction time of 105 minutes.it produced 3.6550 mgNH2-N/ml sample. Proximate composition analysis, functionality tests and sensory evaluation. The product yield moisture, 21.534% protein, 1.6 lipids and 14.38% ash. The solubility of the product in water is 43.02% and its water activity is equal to 0.76. The indole concentration of the raw marerials and product is equal to 0.3053 and 0.3092 respectively, thus it is safe for human consumption.